Cognitive functioning in socially anxious adults: insights from the NIH Toolbox Cognition Battery - Troller-Renfree, Sonya V.; Barker, Tyson V.; Pine, Daniel S.; Fox, Nathan A. (Frontiers in Psychology, 2015)
Theory suggests that individuals with social anxiety manifest unique patterns of cognition with less efficient fluid cognition and unperturbed crystallized cognition; however, empirical support for these ideas remains inconclusive. The heterogeneity of past findings may reflect unreliability in cognitive assessments or the influence of confounding variables. The present study examined the relations among social anxiety and performance on the reliable, newly established NIH Toolbox Cognition Battery. Results indicate that high socially anxious adults performed as well as low anxious participants on all measures of fluid cognition. However, highly socially anxious adults demonstrated enhanced crystallized cognitive abilities relative to a low socially anxious comparison group.